Left Anterior Temporal Glucose Metabolism and not Amyloid-beta Load Predicts Naming Impairment in Alzheimer’s Disease - Frings, Lars; S. Spehl, Timo; Hüll, Michael; T. Meyer, Philipp (Current Alzheimer Research, 2016)
Naming impairment in Alzheimer’s disease dementia (AD) is associated with atrophy of the left anterior temporal lobe (ATL). We aimed to elucidate if regional cerebral glucose metabolism, as a biomarker of synaptic dysfunction and neurodegeneration, of the left ATL predicts naming impairment, and if amyloid-beta (Aβ) deposition, a pathological hallmark of AD, contributes to the prediction. Twenty-nine patients with AD underwent combined [11C]PIB and [18F]FDG PET examinations for assessment of Aβ load and regional cerebral glucose metabolism. An a priori defined region of interest was used for regional PET analyses of the left ATL. In linear stepwise regression analyses, glucose metabolism of the left ATL was the only significant predictor of naming performance, independent of sex, age, and education. Neither regional nor global Aβ load contributed to the prediction. Left ATL glucose metabolism predicts naming impairment in AD. By contrast, Aβ deposition does not predict naming impairment.
Keywords: Pittsburgh compound B